Mengenal Jenis-Jenis Teleskop dan Penggunaannya - Irvan ,; Leo Hermawan (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2019)
Astronomy is a study of the sky. In the development of astronomy and the development of times in the field of science, many astronomical instruments were found, which were useful in research in the field of astronomy. One of the most popular and cannot be taken from astronomy is the telescope. The beginning of the discovery of the telescope originated from its discovery, and at that time a discovery was made that could be used in observing distant objects known with optical telescopes. The more advanced the development of technology, the telescope was found with a new model that uses elekromagnektik waves obtained from radio waves, this telescope is known as a radio telescope. Keywords: Astronomy, Optical Telescope, Radio Telescope